Effect of sodium oleate on the agglomeration of calcium carbonate - SAYAN, PERVİZ (WILEY-V C H VERLAG GMBH, 2005)
The effect of Na-Oleate on the agglomeration of calcium carbonate was investigated. Oleate is determined by Infrared spectroscopy. In order to detect the amount of Oleate adsorbed on the calcium carbonate crystals, the differential thermal analysis method was used. The agglomerate size and zeta potential were investigated as a function of Na-Oleate concentration and pH value. It was found that the amount of Na-Oleate adsorbed on the calcium carbonate is not only depending on the concentration but also on the pH value and zeta potential, The results also show that the critical Na-Oleate concentration, where the maximum Na-Oleate adsorption was reached, was found approximately 300 ppm under the selected experimental condition. (c) 2005 WILEY-VCH Verlag GmbH T Co. KGaA, Weinheim.
Keywords: Na-Oleate; agglomeration; calcium carbonate; differential thermal analysis; SPHERICAL AGGLOMERATION; PRECIPITATION; SUSPENSIONS